Implementasi Metode OCRA Penentuan Dosen Terbaik Dimasa Pandemi Covid-19 - Tanjung, Dewi Maulida Sari; Al-Adawiyah, Robiah; Saputra, Imam (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Each lecturer has a different way of teaching, some are preferred by students and some are not liked by students. A lecturer is required to improve his performance in teaching and imparting the knowledge he has to his students, so there are several requirements that are used as criteria in determining the best lecturers including Doc Scopus, Position, Competence, Age, and Warning Letters. So that in this study a money system was made using a decision support system that could determine the best lecturers during the covid-19 pandemic. In its determination, data such as criteria, weights and alternatives are needed. So, in this study using the OCRA (Optional Competitiveness Rating Analysis) method to determine the Best Lecturer through data such as alternatives and criteria, it can be concluded that the second alternative (A2) is Kennedi as the best Lecturer with the best preference value of 3,837.